STRATEGI BIAYA PRODUKSI DAN PROMOSI DALAM MENINGKATKAN LABA: STUDI EMPIRIS PADA PT ULTRAJAYA MILK INDUSTRY, TBK - Agbert Zega; Budi Gautama Siregar; Zulaika Matondang; Aswadi Lubis (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2025)
This study aims to analyze the influence of production cost and promotion cost strategies on the company's profit at PT Ultrajaya Milk Industry Tbk during the period 2015–2023. Secondary data is obtained from the company's financial statements and analyzed using the multiple linear regression method. The results show that production costs have a significant and positive influence on profits, which indicates that increasing efficiency in the production process directly increases the company's profit margins. On the other hand, promotional costs do not show a significant influence on profits, indicating that the allocation of promotional budgets has not been effective in driving increased sales. These findings have practical implications for management to prioritize efforts to improve production cost efficiency and conduct in-depth evaluations of promotional strategies to increase their effectiveness. Suggestions for further research include developing a model by incorporating additional variables, such as product innovation, distribution channels, and market competition dynamics, to gain a more comprehensive understanding of the factors that affect a company's bottom line.